The cymothoid isopod Anilocra chromis is negatively associated with multiple metrics of host condition in the Caribbean damselfish Chromis multilineata - Jan-Alexis Barry; Kyle G. Jerris; Teresa R. Turner; Jenilee B. Robinson; Matthew D. Nicholson; Paul C. Sikkel (Marine Biology, 2026)
Parasitism is widespread among fishes in nature and can have significant impacts on individuals, populations, and communities. The family Cymothoidae includes over 380 species of parasitic isopods that infect a wide variety of host fishes, mostly in tropical and subtropical oceans. Despite their conspicuous nature, spatiotemporal patterns of infestation and effects on hosts have been studied for only a small percentage of species. The brown chromis ( Chromis multilineata ) is a common planktivorous damselfish associated with reefs in the tropical western Atlantic. Brown chromis are frequently infested with the large cymothoid isopod Anilocra chromis. In this study, we quantified the prevalence of infection among five sites and over two years in the US Virgin Islands (before and after major hurricanes). We further quantified the relationship between Anilocra infection status and the coinfection of other parasites as well as three metrics of potential impact: gonadal development, rate of food intake, and locomotion. Our results show that parasite prevalence differed significantly among sites. Additionally, while there was variation in coinfection with other parasites among sites, there was no relationship between the presence of Anilocra and the abundance of other parasites. There was a significant negative effect of Anilocra infection on male chromis gonads, feeding behavior (as determined by a decrease in bite-rates), and locomotion (as determined by an increase in fin-beats). Overall, these findings suggest that parasitism by Anilocra chromis is negatively associated with multiple metrics of fitness and health in host fishes, and thus likely has consequences at the population level.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Identification of evidence gaps and future research needs in food safety - E. Burton; S.P. Borriello; P.J. Gregory; J. Healing; C. Nicholson; T.H. Oliver; S. Pearson; R. Smith; M. Tildesley; J. Wastling; J. O'Brien (Trends in Food Science & Technology, 2026)

Wild bees mediate fruit quality via seed set in highbush blueberry: A quantitative synthesis - Maxime Eeraerts; Clark Kogan; Rufus Isaacs; Péter Batáry; Brett R. Blaauw; Kyle Bobiwash; Joshua W. Campbell; Pablo Cavigliasso; Jaret C. Daniels; James D. Ellis; Jason Gibbs; Lauren Goldstein; et al. (Agriculture, Ecosystems & Environment, 2025)

Applying the IUCN Global Ecosystem Typology to classify, describe, and map ecosystems based on regional data and Indigenous knowledge - Alys R. Young; Hugh F. Davies; Margaret L. Ayre; Alana Brekelmans; Brett A. Bryan; Jane Elith; Kate Hadden; Mavis Kerinaiua; David A. Keith; Donna L. Lewis; Kinjia M. Munkara‐Murray; Sarah Ryan; et al. (Conservation Biology, 2025)
Effective ecosystem conservation for biodiversity and human well‐being relies on accurate information. Consistent approaches to classifying, describing, and assessing ecosystems can improve understanding of ecological processes, threats, and management. We explored how the International Union for Conservation of Nature (IUCN) Global Ecosystem Typology—a global classification framework based on ecosystem function—could support the development of a classification of ecosystems for the Tiwi Islands, Australia, by incorporating scientific information and Indigenous Tiwi knowledge to facilitate environmental management and conservation. We synthesized ecosystem information from previous research, field data, reports, and Tiwi knowledge authorities to develop a classification, descriptions, and a map of 14 terrestrial ecosystem types. These ecosystem types were defined and described based on ecological processes and were broader yet largely congruent with existing vegetation classifications. Including functional properties accounted for variation in the vegetation physiognomy exhibited by dynamic and disturbance‐prone ecosystems, such as savannas. Because we considered Tiwi knowledge authorities and the IUCN Global Ecosystem Typology, our inventory included ecosystem types that were typically omitted from previous classifications, which should allow for more comprehensive assessments and management. Relating the new ecosystem typology to the IUCN Global Ecosystem Typology will facilitate comparisons among similar ecosystems, regarding, for example, effective threat abatement options. Describing the biota and processes opens new avenues for monitoring. More collaborative work is needed to explore how Western scientific ecosystem inventories operate alongside and in connection with management of Tiwi murrakupuni enacted by Tiwi people. Given the ongoing loss of biodiversity, ecosystem management must draw on information across domains, scales, and knowledge systems. We demonstrated an approach to this task and provided socioecologically relevant ecosystem information.

Increased quadriceps intermuscular adipose tissue in chronic liver disease is associated with an altered muscle transcriptome compared with healthy age matched controls - J. I. Quinlan; T. Nicholson; C. Bell; A. Dhaliwal; F. R. Williams; S. L. Allen; S. Choudhary; A. V. Rowlands; A. M. Elsharkawy; M. J. Armstrong; C. A. Greig; J. M. Lord; et al. (GeroScience, 2025)
Muscle fat infiltration (i.e., myosteatosis) is an important index of muscle health and pathology in disease states, such as chronic liver disease (CLD). However, it is unknown whether myosteatosis differs due to anatomical location. Further, the mechanistic implications of divergent intermuscular adipose tissue (IMAT) deposition remain unknown in patients with CLD. Thirty-three patients with CLD (55.0 ± 10.5 years) and 17 healthy controls (HC) (49.6 ± 15.4 years) were recruited. Quadriceps IMAT was estimated between 20 and 80% of muscle length and psoas IMAT at L3 via MRI. Body composition, muscle strength, and habitual activity were assessed. Fasted vastus lateralis muscle biopsies were collected and subjected to RNA sequencing analysis. ClinicalTrials.gov identifier: NCT04734496. IMAT was greater in CLD compared with HC in both quadriceps and psoas ( P < 0.0001). Quadriceps IMAT positively correlated with BMI ( r = 0.62), body fat ( r = 0.65), age ( r = 0.36), and negatively correlated with maximal knee extensor strength ( r = −0.45) and habitual physical activity ( r = −0.50) in CLD and HC. One hundred sixty-nine differentially expressed genes (DEGs) were identified in low IMAT CLD vs. HC, and 178 DEGs were identified in high IMAT CLD vs. HC. CLD patients with high and low IMAT exhibited defined expression profiles, with only 39 DEGs (representing 12.7%) in common. Pathway analysis of DEGs revealed enrichment of atrophic and pro-inflammatory pathways in the high IMAT group. IMAT is greater in patients with CLD compared to HC, irrespective of anatomical location, and is associated with reductions in muscle function and may be exacerbated by physical inactivity. IMAT appears to alter the muscle transcriptome in COLD, potentially exacerbating muscle loss. Graphical Abstract

Exposure and health risks of benzene from combustion by gas stoves: A modelling approach in U.S. homes - Anchal Garg; Yannai Kashtan; Metta Nicholson; Colin J. Finnegan; Eric D. Lebel; Drew R. Michanowicz; Seth B.C. Shonkoff; Kari C. Nadeau; Robert B. Jackson (Journal of Hazardous Materials, 2025)

The impact of measuring conditions on the relationship between sensory and measured juiciness in plant-based burgers - Raisa E.D. Rudge; Felix Briner; Reed A. Nicholson; Colleen Cottrell; Janet Collins; Louwrens C. Hoffman; Jason R. Stokes; Heather E. Smyth (Food Hydrocolloids, 2025)

Characteristics of volcanic ash reveal changes in fragmentation and eruption dynamics at Poás Volcano, Costa Rica, 2016–2019 - Monserrat Cascante; Thomas Giachetti; Heather Michelle Nicholson Wright; Alexa R. Van Eaton; Geoffroy Avard (Bulletin of Volcanology, 2025)
Determining whether fresh magma has reached the surface during a volcanic eruption can provide important information for forecasts of future activity, especially in the early stages of an eruption. However, identifying fresh, juvenile pyroclasts in tephra fall deposits can be challenging and inconclusive. We studied the products of explosions at Poás Volcano, Costa Rica, in 2016–2019, a period during which the volcano transitioned from a pressurized, hydrothermally sealed state to an open conduit with increased degassing to the atmosphere. The activity consisted of semi-continuous explosions producing < 500-m-high plumes, with the exception of explosions on April 14 and 22, 2017, that produced 4-km-high plumes. We analyzed the grain size distribution, componentry, and particle density of the products of twenty explosions, and collected groundmass glass composition on juvenile particles for three of them. Our work demonstrates varying degrees of magma involvement with the hydrothermal system through time, with juvenile material representing a wide range of abundance (~ 10–70 vol.%) in deposits of individual explosions. Before early April 2017, we infer that small phreatomagmatic explosions were triggered by contact between magmatic fluids and/or magma and the hydrothermal system, based on the presence of abundant hydrothermal fragments and minor juvenile magma. Concurrent with decreasing hydrothermal component in the deposits, explosions in April–May 2017 eroded the walls of the shallow plumbing system, evidenced by an increase in wall-rock lithics in the deposits. These changes coincided with drying of the crater lake, leading to several magmatic explosions in April-September 2017, whose juvenile-rich deposits are consistent with primary fragmentation of fresh magma in the conduit. The eruptive activity changed after this magmatic phase, and in 2019, small explosions mostly recycled the heterogeneous deposits of previous events, producing fine material with high proportions of recycled particles. All explosions from 2016 to 2019 remobilized already-emplaced magma from the 1953–1955 eruptive period, although distinct glass compositions between explosions suggest difference in crystallization or they tapped different portions of this magma body. Our work sheds light on the eruption dynamics and shallow plumbing system of this persistently active volcano and provides a case study for understanding the variable efficiency of phreatomagmatic fragmentation.

Uncrewed surface vehicles in the Global Ocean Observing System: a new frontier for observing and monitoring at the air-sea interface - Ruth G. Patterson; Meghan F. Cronin; Sebastiaan Swart; Joana Beja; Johan M. Edholm; Jason McKenna; Jaime B. Palter; Alex Parker; Charles I. Addey; Wieter Boone; Paban Bhuyan; Justin J. H. Buck; et al. (Frontiers in Marine Science, 2025)
Observing air-sea interactions on a global scale is essential for improving Earth system forecasts. Yet these exchanges are challenging to quantify for a range of reasons, including extreme conditions, vast and remote under-sampled locations, requirements for a multitude of co-located variables, and the high variability of fluxes in space and time. Uncrewed Surface Vehicles (USVs) present a novel solution for measuring these crucial air-sea interactions at a global scale. Powered by renewable energy (e.g., wind and waves for propulsion, solar power for electronics), USVs have provided navigable and persistent observing capabilities over the past decade and a half. In our review of 200 USV datasets and 96 studies, we found USVs have observed a total of 33 variables spanning physical, biogeochemical, biological and ecological processes at the air-sea transition zone. We present a map showing the global proliferation of USV adoption for scientific ocean observing. This review, carried out under the auspices of the ‘Observing Air-Sea Interactions Strategy’ (OASIS), makes the case for a permanent USV network to complement the mature and emerging networks within the Global Ocean Observing System (GOOS). The Observations Coordination Group (OCG) overseeing GOOS has identified ten attributes of an in-situ global network. Here, we discuss and evaluate the maturation of the USV network towards meeting these attributes. Our article forms the basis of a roadmap to formalise and guide the global USV community towards a novel and integrated ocean observing frontier.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Demographic History and Adaptive Evolution of Indo‐Pacific Bottlenose Dolphins ( Tursiops aduncus ) in Western Australia - Svenja M. Marfurt; Delphine B. H. Chabanne; Samuel Wittwer; Manuela R. Bizzozzero; Simon J. Allen; Livia Gerber; Krista Nicholson; Michael Krützen (Molecular Ecology, 2024)
Demographic processes can substantially affect a species' response to changing ecological conditions, necessitating the combined consideration of genetic responses to environmental variables and neutral genetic variation. Using a seascape genomics approach combined with population demographic modelling, we explored the interplay of demographic and environmental factors that shaped the current population structure in Indo‐Pacific bottlenose dolphins ( Tursiops aduncus ) along the Western Australian coastline. We combined large‐scale environmental data gathered via remote sensing with RADseq genomic data from 133 individuals at 19 sampling sites. Using population genetic and outlier detection analyses, we identified three distinct genetic clusters, coinciding with tropical, subtropical and temperate provincial bioregions. In contrast to previous studies, our demographic models indicated that populations occupying the paleo‐shoreline split into two demographically independent lineages before the last glacial maximum (LGM). A subsequent split after the LGM 12—15 kya gave rise to the Shark Bay population, thereby creating the three currently observed clusters. Although multi‐locus heterozygosity declined from north to south, dolphins from the southernmost cluster inhabiting temperate waters had higher heterozygosity in potentially adaptive loci compared to dolphins from subtropical and tropical waters. These findings suggest ongoing adaptation to cold‐temperate waters in the southernmost cluster, possibly linked to distinct selective pressures between the different bioregions. Our study demonstrated that in the marine realm, without apparent physical boundaries, only a combined approach can fully elucidate the intricate environmental and genetic interactions shaping the evolutionary trajectory of marine mammals.

Magma recharge at Manam volcano, Papua New Guinea, identified through thermal and SO2 satellite remote sensing of open-vent emissions - Adam S. Cotterill; Emma J. Nicholson; Catherine S. L. Hayer; Christopher R. J. Kilburn (Bulletin of Volcanology, 2024)
Manam is one of the most frequently active volcanoes in Papua New Guinea and is a top contributor to global volcanic volatile emissions due to its persistent open-vent degassing. Here, we present a multi-year time series (2018–2021) of thermal and SO 2 emissions for Manam from satellite remote sensing, which we interpret in the context of open-vent feedback between magma supply, reservoir pressure, and outgassing. We classify the time series into four phases based on the varying SO 2 flux and observe a transient, yet substantial, increase in time-averaged SO 2 flux from background levels of ~ 0.6 to ~ 4.72 kt day −1 between March and July 2019. We also identify a transition from temporally coupled to decoupled gas and thermal emissions during this period which we explain in the context of a magma recharge event that supplied new, volatile-rich magma to the shallow plumbing system beneath Manam. We infer that the arrival of this recharge magma triggered the series of eruptions between August 2018 and March 2019. These explosive events collectively removed 0.18 km 3 of degassed residual magma and signalled the onset of a renewed period of unrest that ultimately culminated in a major eruption on 28 June 2019. We quantify the magnitude of “excess” degassing at Manam after the removal of the inferred residual magma. SO 2 emissions reveal that ~ 0.18 km 3 of magma was supplied, but only ~ 0.08 km 3 was erupted between April 2019 and December 2021. We highlight how multi-parameter remote sensing observations over months to years enable the interpretation of open-vent processes that may be missed by short-duration campaign measurements.

Hypocretin-1 receptor antagonism improves inhibitory control during the Go/No-Go task in highly motivated, impulsive male mice - Jeremy Metha; Yijun Ji; Clemens Braun; Janet R. Nicholson; Luis De Lecea; Carsten Murawski; Daniel Hoyer; Laura H. Jacobson (Psychopharmacology, 2024)
Rationale Motivation and inhibitory control are dominantly regulated by the dopaminergic (DA) and noradrenergic (NA) systems, respectively. Hypothalamic hypocretin (orexin) neurons provide afferent inputs to DA and NA nuclei and hypocretin-1 receptors (HcrtR1) are implicated in reward and addiction. However, the role of the HcrtR1 in inhibitory control is not well understood. Objectives To determine the effects of HcrtR1 antagonism and motivational state in inhibitory control using the go/no-go task in mice. Methods n = 23 male C57Bl/6JArc mice were trained in a go/no-go task. Decision tree dendrogram analysis of training data identified more and less impulsive clusters of animals. A HcrtR1 antagonist (BI001, 12.5 mg/kg, per os ) or vehicle were then administered 30 min before go/no-go testing, once daily for 5 days, under high (food-restricted) and low (free-feeding) motivational states in a latin-square crossover design. Compound exposure levels were assessed in a satellite group of animals. Results HcrtR1 antagonism increased go accuracy and decreased no-go accuracy in free-feeding animals overall, whereas it decreased go accuracy and increased no-go accuracy only in more impulsive, food restricted mice. HcrtR1 antagonism also showed differential effects in premature responding, which was increased in response to the antagonist in free-feeding, less impulsive animals, and decreased in food restricted, more impulsive animals. HcrtR1 receptor occupancy by BI001 was estimated at ~ 66% during the task. Conclusions These data indicate that hypocretin signalling plays roles in goal-directed behaviour and inhibitory control in a motivational state-dependant manner. While likely not useful in all settings, HcrtR1 antagonism may be beneficial in improving inhibitory control in impulsive subpopulations.

Pollination deficits and their relation with insect pollinator visitation are cultivar-dependent in an entomophilous crop - Maxime Eeraerts; Stan Chabert; Lisa W. DeVetter; Péter Batáry; John J. Ternest; Kris Verheyen; Kyle Bobiwash; Kayla Brouwer; Daniel García; G. Arjen de Groot; Jason Gibbs; Lauren Goldstein; et al. (Agriculture, Ecosystems & Environment, 2024)

Mitigating water pollution: tourists’ willingness to pay for eco-friendly toilets in the Sagarmatha National Park, Mt. Everest area, Nepal - Steven R. Hall; Kirsten Nicholson; Misa Nishikawa (Environment, Development and Sustainability, 2024)

Assessing how metal reef restoration structures shape the functional and taxonomic profile of coral-associated bacterial communities - Paige Strudwick; David J. Suggett; Justin R. Seymour; Matthew Z. DeMaere; Amanda Grima; John Edmondson; Alicia McArdle; Freda Nicholson; Emma F. Camp (Frontiers in Marine Science, 2024)
Significant threats to the long-term persistence of coral reefs have accelerated the adoption of coral propagation and out-planting approaches. However, how materials commonly used for propagation structures could potentially affect coral-associated bacterial communities remains untested. Here, we examined the impact of metal propagation structures on coral-associated bacterial communities. Fragments of the coral species Acropora millepora were grown on aluminium, sand/epoxy-coated steel (Reef Stars), and uncoated steel (rebar) structures. After 6 months, the functional and taxonomic profiles of coral-associated bacterial communities of propagated corals and reef colonies were characterised using amplicon (16S rRNA gene) and shotgun metagenomic sequencing. No differences in the phylogenetic structure or functional profile of coral-associated bacterial communities were observed between propagated corals and reef colonies. However, specific genes and pathways (e.g., lipid, nucleotide, and carbohydrate metabolism) were overrepresented in corals grown on different materials, and different taxa were indicative of the materials. These findings indicate that coral propagation on different materials may lead to differences in the individual bacterial taxa and functional potential of coral-associated bacterial communities, but how these contribute to changed holobiont fitness presents a key question to be addressed.

Using the system of environmental-economic accounting ecosystem accounting for policy: A case study on forest ecosystems - S. King; R. Agra; A. Zolyomi; H. Keith; E. Nicholson; X. de Lamo; R. Portela; C. Obst; M. Alam; M. Honzák; R. Valbuena; P.A.L.D. Nunes; et al. (Environmental Science & Policy, 2024)

Assessment of oceanographic conditions during the North Atlantic EXport processes in the ocean from RemoTe sensing (EXPORTS) field campaign - Leah Johnson; David A. Siegel; Andrew F. Thompson; Erik Fields; Zachary K. Erickson; Ivona Cetinic; Craig M. Lee; Eric A. D'Asaro; Norman B. Nelson; Melissa M. Omand; Michaela Sten; Shawnee Traylor; et al. (Progress in Oceanography, 2024)

Evidence for density‐dependent effects on body composition of a large omnivore in a changing Greater Yellowstone Ecosystem - Andrea Corradini; Mark A. Haroldson; Francesca Cagnacci; Cecily M. Costello; Daniel D. Bjornlie; Daniel J. Thompson; Jeremy M. Nicholson; Kerry A. Gunther; Katharine R. Wilmot; Frank T. van Manen (Global Change Biology, 2023)
Understanding the density‐dependent processes that drive population demography in a changing world is critical in ecology, yet measuring performance–density relationships in long‐lived mammalian species demands long‐term data, limiting scientists' ability to observe such mechanisms. We tested performance–density relationships for an opportunistic omnivore, grizzly bears ( Ursus arctos , Linnaeus, 1758) in the Greater Yellowstone Ecosystem, with estimates of body composition (lean body mass and percent body fat) serving as indicators of individual performance over two decades (2000–2020) during which time pronounced environmental changes have occurred. Several high‐calorie foods for grizzly bears have mostly declined in recent decades (e.g., whitebark pine [ Pinus albicaulis , Engelm, 1863]), while increasing human impacts from recreation, development, and long‐term shifts in temperatures and precipitation are altering the ecosystem. We hypothesized that individual lean body mass declines as population density increases (H1), and that this effect would be more pronounced among growing individuals (H2). We also hypothesized that omnivory helps grizzly bears buffer energy intake from changing foods, with body fat levels being independent from population density and environmental changes (H3). Our analyses showed that individual lean body mass was negatively related to population density, particularly among growing‐age females, supporting H1 and partially H2. In contrast, population density or sex had little effect on body fat levels and rate of accumulation, indicating that sufficient food resources were available on the landscape to accommodate successful use of shifting food sources, supporting H3. Our results offer important insights into ecological feedback mechanisms driving individual performances within a population undergoing demographic and ecosystem‐level changes. However, synergistic effects of continued climate change and increased human impacts could lead to more extreme changes in food availability and affect observed population resilience mechanisms. Our findings underscore the importance of long‐term studies in protected areas when investigating complex ecological relationships in an increasingly anthropogenic world.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Detecting forest response to droughts with global observations of vegetation water content - Alexandra G. Konings; Sassan S. Saatchi; Christian Frankenberg; Michael Keller; Victor Leshyk; William R. L. Anderegg; Vincent Humphrey; Ashley M. Matheny; Anna Trugman; Lawren Sack; Elizabeth Agee; Mallory L. Barnes; et al. (Global Change Biology, 2021)
Droughts in a warming climate have become more common and more extreme, making understanding forest responses to water stress increasingly pressing. Analysis of water stress in trees has long focused on water potential in xylem and leaves, which influences stomatal closure and water flow through the soil‐plant‐atmosphere continuum. At the same time, changes of vegetation water content (VWC) are linked to a range of tree responses, including fluxes of water and carbon, mortality, flammability, and more. Unlike water potential, which requires demanding in situ measurements, VWC can be retrieved from remote sensing measurements, particularly at microwave frequencies using radar and radiometry. Here, we highlight key frontiers through which VWC has the potential to significantly increase our understanding of forest responses to water stress. To validate remote sensing observations of VWC at landscape scale and to better relate them to data assimilation model parameters, we introduce an ecosystem‐scale analog of the pressure–volume curve, the non‐linear relationship between average leaf or branch water potential and water content commonly used in plant hydraulics. The sources of variability in these ecosystem‐scale pressure‐volume curves and their relationship to forest response to water stress are discussed. We further show to what extent diel, seasonal, and decadal dynamics of VWC reflect variations in different processes relating the tree response to water stress. VWC can also be used for inferring belowground conditions—which are difficult to impossible to observe directly. Lastly, we discuss how a dedicated geostationary spaceborne observational system for VWC, when combined with existing datasets, can capture diel and seasonal water dynamics to advance the science and applications of global forest vulnerability to future droughts.

Combating ecosystem collapse from the tropics to the Antarctic - Dana M. Bergstrom; Barbara C. Wienecke; John van den Hoff; Lesley Hughes; David B. Lindenmayer; Tracy D. Ainsworth; Christopher M. Baker; Lucie Bland; David M. J. S. Bowman; Shaun T. Brooks; Josep G. Canadell; Andrew J. Constable; et al. (Global Change Biology, 2021)
Globally, collapse of ecosystems—potentially irreversible change to ecosystem structure, composition and function—imperils biodiversity, human health and well‐being. We examine the current state and recent trajectories of 19 ecosystems, spanning 58° of latitude across 7.7 M km 2 , from Australia's coral reefs to terrestrial Antarctica. Pressures from global climate change and regional human impacts, occurring as chronic ‘presses’ and/or acute ‘pulses’, drive ecosystem collapse. Ecosystem responses to 5–17 pressures were categorised as four collapse profiles—abrupt, smooth, stepped and fluctuating. The manifestation of widespread ecosystem collapse is a stark warning of the necessity to take action. We present a three‐step assessment and management framework (3As Pathway Awareness , Anticipation and Action ) to aid strategic and effective mitigation to alleviate further degradation to help secure our future.

Finding Oxford’s medieval Jewry using organic residue analysis, faunal records and historical documents - J. Dunne; E. Biddulph; P. Manix; T. Gillard; H. Whelton; S. Teague; C. Champness; L. G. Broderick; R. Nicholson; P. Blinkhorn; E. Craig-Atkins; B. Jervis; et al. (Archaeological and Anthropological Sciences, 2021)
Food is often one of the most distinctive expressions of social, religious, cultural or ethnic groups. However, the archaeological identification of specific religious dietary practices, including the Jewish tradition of keeping kosher , associated with ritual food practices and taboos, is very rare. This is arguably one of the oldest known diets across the world and, for an observant Jew, maintaining dietary laws (known as Kashruth) is a fundamental part of everyday life. Recent excavations in the early medieval Oxford Jewish quarter yielded a remarkable assemblage of animal bones, marked by a complete absence of pig specimens and a dominance of kosher (permitted) birds, domestic fowl and goose. To our knowledge, this is the first identification of a Jewish dietary signature in British zooarchaeology, which contrasted markedly with the previous Saxon phase where pig bones were present in quantity and bird bones were barely seen. Lipid residue analysis of pottery from St Aldates showed that vessels from the possible Jewish houses were solely used to process ruminant carcass products, with an avoidance of pig product processing, correlating well with the faunal data. In contrast, lipid analysis of pottery from comparative assemblages from the previous Saxon phase at the site and a contemporaneous site in the city, The Queen’s College, shows that the majority of these vessels appear to have been used to process mixtures of both ruminant and non-ruminant (pig) products. Here, the combination of organic residue analysis, site excavation and animal and fish bone evidence was consistent with the presence of Jewish houses in eleventh- and twelfth-century St Aldates, Oxford, hitherto only suspected through documentary information. This is the first identification of specific religious dietary practices using lipid residue analysis, verifying that, at least 800 years ago, medieval Jewish Oxford communities practised dietary laws known as Kashruth.

α-Parvin and β-parvin in the rat uterus during decidualisation and uterine receptivity - Leigh Nicholson; Romanthi Madawala; Laura Lindsay; Christopher R. Murphy (Histochemistry and Cell Biology, 2019)

Establishment and characterisation of a stavudine (d4T)-induced rat model of antiretroviral toxic neuropathy (ATN) using behavioural and pharmacological methods - Andy Kuo; Janet R. Nicholson; Laura Corradini; Maree T. Smith (Inflammopharmacology, 2019)

Precision application techniques reduce ammonia emissions following food-based digestate applications to grassland - F. A. Nicholson; A. Bhogal; A. Rollett; M. Taylor; J. R. Williams (Nutrient Cycling in Agroecosystems, 2018)

Revisiting the taxonomy of the genus Elizabethkingia using whole-genome sequencing, optical mapping, and MALDI-TOF, along with proposal of three novel Elizabethkingia species: Elizabethkingia bruuniana sp. nov., Elizabethkingia ursingii sp. nov., and Elizabethkingia occulta sp. nov. - Ainsley C. Nicholson; Christopher A. Gulvik; Anne M. Whitney; Ben W. Humrighouse; James Graziano; Brian Emery; Melissa Bell; Vladimir Loparev; Phalasy Juieng; Jarrett Gartin; Chantal Bizet; Dominique Clermont; et al. (Antonie van Leeuwenhoek, 2018)

Expansion of landscape characterisation methods within the Hydrogeological Landscape Framework: application in the Australian Capital Territory - A. L. Cowood; C. L. Moore; M. J. Cracknell; J. Young; R. Muller; A. T. Nicholson; A. C. Wooldridge; B. R. Jenkins; W. Cook (Australian Journal of Earth Sciences, 2017)

Characterisation of Peptide5 systemic administration for treating traumatic spinal cord injured rats - Yilin Mao; Tara Nguyen; Ryan S. Tonkin; Justin G. Lees; Caitlyn Warren; Simon J. O’Carroll; Louise F. B. Nicholson; Colin R. Green; Gila Moalem-Taylor; Catherine A. Gorrie (Experimental Brain Research, 2017)

Experimental evolution of Bacillus subtilis - Daniel R. Zeigler; Wayne L. Nicholson (Environmental Microbiology, 2017)
Summary The endospore‐forming bacteria have persisted on earth perhaps 3Ga, leveraging the flexibility of their distinctive lifestyle to adapt to a remarkably wide range of environments. This process of adaptation can be investigated through the simple but powerful technique of laboratory evolution. Evolved strains can be analyzed by whole genome sequencing and an array of omics technologies. The intensively studied, genetically tractable endospore‐former, Bacillus subtilis , is an ideal subject for laboratory evolution experiments. Here, we describe the use of the B. subtilis model system to study the adaptation of these bacteria to reduced and stringent selection for endospore formation, as well as to novel environmental challenges of low atmospheric pressure, high ultraviolet radiation, and unfavourable growth temperatures. In combination with other approaches, including comparative genomics and environmental field work, laboratory evolution may help elucidate how these bacteria have so successfully adapted to life on earth, and perhaps beyond.

Potentiation of the NO-cGMP pathway and blood flow responses during dynamic exercise in healthy humans - Jacqueline K. Limberg; Katherine R. Malterer; J. Mikhail Kellawan; William G. Schrage; Brad W. Wilkins; Wayne T. Nicholson; John H. Eisenach; Michael J. Joyner; Timothy B. Curry (European Journal of Applied Physiology, 2017)

Mapping a Type 1 FHB resistance on chromosome 4AS of Triticum macha and deployment in combination with two Type 2 resistances - C. Burt; A. Steed; N. Gosman; M. Lemmens; N. Bird; R. Ramirez-Gonzalez; S. Holdgate; P. Nicholson (Theoretical and Applied Genetics, 2015)

Dissociable effects of mGluR5 allosteric modulation on distinct forms of impulsivity in rats: interaction with NMDA receptor antagonism - Sarah N. Isherwood; Anton Pekcec; Janet R. Nicholson; Trevor W. Robbins; Jeffrey W. Dalley (Psychopharmacology, 2015)

Risk factors for endometrial cancer in black and white women: a pooled analysis from the epidemiology of endometrial cancer consortium (E2C2) - Michele L. Cote; Tala Alhajj; Julie J. Ruterbusch; Leslie Bernstein; Louise A. Brinton; William J. Blot; Chu Chen; Margery Gass; Sarah Gaussoin; Brian Henderson; Eunjung Lee; Pamela L. Horn-Ross; et al. (Cancer Causes & Control, 2015)

Method Transfer, Partial Validation, and Cross Validation: Recommendations for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Team - R. J. Briggs; R. Nicholson; F. Vazvaei; J. Busch; M. Mabuchi; K. S. Mahesh; M. Brudny-Kloeppel; N. Weng; P. A. R. Galvinas; P. Duchene; Pei Hu; R. W. Abbott (The AAPS Journal, 2014)

Comprehensive Ubiquitin E2 Profiling of Ten Ubiquitin E3 Ligases - Jeffrey G. Marblestone; Samir Butt; Devin M. McKelvey; David E. Sterner; Michael R. Mattern; Benjamin Nicholson; Michael J. Eddins (Cell Biochemistry and Biophysics, 2013)

“Modeling the impact of natural resource-based poverty traps on food security in Kenya: The Crops, Livestock and Soils in Smallholder Economic Systems (CLASSES) model” - Emma C. Stephens; Charles F. Nicholson; Douglas R. Brown; David Parsons; Christopher B. Barrett; Johannes Lehmann; David Mbugua; Solomon Ngoze; Alice N. Pell; Susan J. Riha (Food Security, 2012)

Spatial and temporal interactions of sympatric mountain lions in Arizona - Kerry L. Nicholson; Paul R. Krausman; Adrian Munguia-Vega; Melanie Culver (European Journal of Wildlife Research, 2011)

The Tyndall coastal simulator - Mustafa Mokrech; Susan Hanson; Robert J. Nicholls; Judith Wolf; Mike Walkden; Corentin M. Fontaine; Sophie Nicholson-Cole; Simon R. Jude; James Leake; Peter Stansby; Andrew R. Watkinson; Mark D. A. Rounsevell; et al. (Journal of Coastal Conservation, 2011)

Targeting the Ubiquitin E3 Ligase MuRF1 to Inhibit Muscle Atrophy - Michael J. Eddins; Jeffrey G. Marblestone; K. G. Suresh Kumar; Craig A. Leach; David E. Sterner; Michael R. Mattern; Benjamin Nicholson (Cell Biochemistry and Biophysics, 2011)

The dddP gene, encoding a novel enzyme that converts dimethylsulfoniopropionate into dimethyl sulfide, is widespread in ocean metagenomes and marine bacteria and also occurs in some Ascomycete fungi - J. D. Todd; A. R. J. Curson; C. L. Dupont; P. Nicholson; A. W. B. Johnston (Environmental Microbiology, 2009)
Summary The marine alphaproteobacterium Roseovarius nubinhibens ISM can produce the gas dimethyl sulfide (DMS) from dimethylsulfoniopropionate (DMSP), a widespread secondary metabolite that occurs in many phytoplankton. Roseovarius possesses a novel gene, termed dddP , which when cloned, confers on Escherichia coli the ability to produce DMS. The DddP polypeptide is in the large family of M24 metallopeptidases and is wholly different from two other enzymes, DddD and DddL, which were previously shown to generate DMS from dimethylsulfoniopropionate. Close homologues of DddP occur in other alphaproteobacteria and more surprisingly, in some Ascomycete fungi. These were the biotechnologically important Aspergillus oryzae and the plant pathogen, Fusarium graminearum . The dddP gene is abundant in the bacterial metagenomic sequences in the Global Ocean Sampling Expedition. Thus, dddP has several novel features and is widely dispersed, both taxonomically and geographically.

The dddP gene, encoding a novel enzyme that converts dimethylsulfoniopropionate into dimethyl sulfide, is widespread in ocean metagenomes and marine bacteria and also occurs in some Ascomycete fungi - J. D. Todd; A. R. J. Curson; C. L. Dupont; P. Nicholson; A. W. B. Johnston (Environmental Microbiology, 2009)

Semi-dwarfing Rht-B1 and Rht-D1 loci of wheat differ significantly in their influence on resistance to Fusarium head blight - Srinivasachary; N. Gosman; A. Steed; T. W. Hollins; R. Bayles; P. Jennings; P. Nicholson (Theoretical and Applied Genetics, 2009)

Identification of QTLs for resistance to Fusarium head blight, DON accumulation and associated traits in the winter wheat variety Arina - R. Draeger; N. Gosman; A. Steed; E. Chandler; M. Thomsett; Srinivasachary; J. Schondelmaier; H. Buerstmayr; M. Lemmens; M. Schmolke; A. Mesterhazy; P. Nicholson (Theoretical and Applied Genetics, 2007)

An evaluation of airborne laser scan data for coalmine subsidence mapping - D. R. Palamara; M. Nicholson; P. Flentje; E. Baafi; G. M. Brassington (International Journal of Remote Sensing, 2007)

Aspects of the evolution of Nicotiana tabacum L. and the status of the United States Nicotiana Germplasm Collection - R. S. Lewis; J. S. Nicholson (Genetic Resources and Crop Evolution, 2007)

Hepatotoxin-induced hypertyrosinemia and its toxicological significance - T. Andrew Clayton; John C. Lindon; Jeremy R. Everett; Claude Charuel; Gilles Hanton; Jean-Loic Le Net; Jean-Pierre Provost; Jeremy K. Nicholson (Archives of Toxicology, 2007)

A Method for Extracting RNA from Dormant and Germinating Bacillus subtilis Strain 168 Endospores - R. Moeller; G. Horneck; P. Rettberg; H.-J. Mollenkopf; E. Stackebrandt; W. L. Nicholson (Current Microbiology, 2006)

Observation of a parental inversion variant in a rare Williams–Beuren syndrome family with two affected children - Stephen W. Scherer; Karen W. Gripp; Jaume Lucena; Linda Nicholson; Jean-Paul Bonnefont; Luis A. Pérez-Jurado; Lucy R. Osborne (Human Genetics, 2005)

An Approach to Predict Risks to Wildlife Populations from Mercury and Other Stressors - Diane Nacci; Marguerite Pelletier; Jim Lake; Rick Bennett; John Nichols; Romona Haebler; Jason Grear; Anne Kuhn; Jane Copeland; Matthew Nicholson; Steven Walters; Wayne R. Munns (Ecotoxicology, 2005)

Analysis of the relationship between parameters of resistance to Fusarium head blight and in vitro tolerance to deoxynivalenol of the winter wheat cultivar WEK0609 - N. Gosman; E. Chandler; M. Thomsett; R. Draeger; P. Nicholson (European Journal of Plant Pathology, 2005)

Hepatotoxin-induced hypercreatinaemia and hypercreatinuria: their relationship to one another, to liver damage and to weakened nutritional status - T. Andrew Clayton; John C. Lindon; Jeremy R. Everett; Claude Charuel; Gilles Hanton; Jean-Loic Le Net; Jean-Pierre Provost; Jeremy K. Nicholson (Archives of Toxicology, 2004)

Competitive interactions between Microdochium nivale var. majus , M. nivale var. nivale and Fusarium culmorum in planta and in vitro - Duncan R. Simpson; Martha A. Thomsett; Paul Nicholson (Environmental Microbiology, 2004)
Summary Microdochium nivale var. majus and var. nivale are economically important fungal pathogens of cereal seedlings, stem bases and ears, as is the toxigenic species Fusarium culmorum . Competition experiments on seedlings support an earlier report of differential host preference between the varieties of M. nivale on wheat and rye seedlings at 15°C, but showed that it does not extend across a broad range of temperatures. The studies showed that, although interaction is disadvantageous to the less virulent pathogen, it does not confer an advantage to the more virulent pathogen. In mixed inoculum experiments on wheat seedlings at 15°C and 20°C, F. culmorum suppressed the growth of both varieties of M. nivale . However, if M. nivale var. majus became established on the seedlings, it was able to co‐suppress colonization of wheat seedlings by F. culmorum . In contrast M. nivale var. nivale did not suppress F. culmorum significantly. The growth of M. nivale var. majus and F. culmorum was also co‐suppressed in liquid culture. Significantly, the accumulation of deoxynivalenol mycotoxin was also reduced in the mixed in vitro culture compared with axenic culture of F. culmorum . However, in vitro interaction studies on solidified media were of only limited use in predicting the outcome of competitions in planta .

An hypothesis for a mechanism underlying hepatotoxin-induced hypercreatinuria - T. Andrew Clayton; John C. Lindon; Jeremy R. Everett; Claude Charuel; Gilles Hanton; Jean-Loic Le Net; Jean-Pierre Provost; Jeremy K. Nicholson (Archives of Toxicology, 2003)

Experience with the clinical development of influenza vaccines for potential pandemics - J. Wood; K. Nicholson; I. Stephenson; M. Zambon; R. Newman; D. Major; A. Podda (Medical Microbiology and Immunology, 2002)

Differential Control of Head Blight Pathogens of Wheat by Fungicides and Consequences for Mycotoxin Contamination of Grain - Duncan R. Simpson; Gillian E. Weston; Judith A. Turner; Philip Jennings; Paul Nicholson (European Journal of Plant Pathology, 2001)

HIP12 is a non-proapoptotic member of a gene family including HIP1, an interacting protein with huntingtin - Vikramjit S. Chopra; Martina Metzler; Dita M. Rasper; Asa E.Y. Engqvist-Goldstein; Roshni Singaraja; Lu Gan; Keith M. Fichter; Krista McCutcheon; David Drubin; Donald W. Nicholson; Michael R. Hayden (Mammalian Genome, 2000)

Evaluation of the reinforcing properties and phencyclidine-like discriminative stimulus effects of dextromethorphan and dextrorphan in rats and rhesus monkeys - Katherine L. Nicholson; Belinda A. Hayes; R. L. Balster (Psychopharmacology, 1999)

Nestling obesity in procellariiform seabirds: temporal and stochastic variation in provisioning and growth of short-tailed shearwaters Puffinus tenuirostris - K. C. Hamer; L. W. Nicholson; J. K. Hill; R. D. Wooller; J. S. Bradley (Oecologia, 1997)

Interleukin-1α-converting enzyme (ICE) and related cell death genes ICErel-II and ICErel-III map to the same PAC clone at band 11q22.2-22.3 - Jamal Nasir; Jane L. Theilmann; John P. Vaillancourt; Neil A. Munday; Ambereen Ali; Stephen Scherer; Barbara Beatty; Donald W. Nicholson; Michael R. Hayden (Mammalian Genome, 1997)

The effect of phosphate on the transformation of ferrihydrite into crystalline products in alkaline media - C. R. Paige; W. J. Snodgrass; Ronald V. Nicholson; J. M. Scharer; Q. H. He (Water, Air, & Soil Pollution, 1997)

the effect of phosphate on the transformation of ferrihydrite into crystalline products in alkaline media - C. R. Paige; W. J. Snodgrass; Ronald V. Nicholson; J. M. Scharer; Q. H. He (Water, Air, & Soil Pollution, 1997)

Localization of the cell death genes CPP32 and Mch-2 to human Chromosome 4q - J. Nasir; J. L. Theilmann; V. Chopra; A. M. Jones; D. Walker; D. M. Rasper; J. P. Vaillancourt; J. E. Hewitt; D. W. Nicholson; M. R. Hayden (Mammalian Genome, 1997)

Studies on the comparative toxicity of S-(1,2-dichlorovinyl)-L-cysteine, S-(1,2-dichlorovinyl)-L-homocysteine and 1,1,2-trichloro-3,3,3-trifluoro-1-propene in the Fischer 344 rat - Maria L. Anthony; Christopher R. Beddell; John C. Lindon; Jeremy K. Nicholson (Archives of Toxicology, 1994)

Studies of the biochemical toxicology of uranyl nitratein the rat - Maria L. Anthony; Kevin P. R. Gartland; Christopher R. Beddell; John C. Lindon; Jeremy K. Nicholson (Archives of Toxicology, 1994)

Studies of the biochemical toxicology of uranyl nitrate in the rat - Maria L. Anthony; Kevin P. R. Gartland; Christopher R. Beddell; John C. Lindon; Jeremy K. Nicholson (Archives of Toxicology, 1994)

Studies on the effects ofl(αS,5S)-α-amino-3-chloro-4,5-dihydro-5-isoxazoleacetic acid (AT-125) on 4-aminophenol-induced nephrotoxicity in the Fischer 344 rat - Maria L. Anthony; Christopher R. Beddell; John C. Lindon; Jeremy K. Nicholson (Archives of Toxicology, 1993)

Cephaloridine-induced nephrotoxicity in the Fischer 344 rat: proton NMR spectroscopic studies of urine and plasma in relation to conventional clinical chemical and histopathological assessments of nephronal damage - Maria L. Anthony; Kevin P. R. Gartland; Christopher R. Beddell; John C. Lindon; Jeremy K. Nicholson (Archives of Toxicology, 1992)

Effects of biliary cannulation and buthionine sulphoximine pretreatment on the nephrotoxicity of para-aminophenol in the Fischer 344 rat - K. P. R. Gartland; C. T. Eason; F. W. Bonner; J. K. Nicholson (Archives of Toxicology, 1990)

Biochemical characterisation of para-aminophenol-induced nephrotoxic lesions in the F344 rat - Kevin P. R. Gartland; Frank W. Bonner; John A. Timbrell; Jeremy K. Nicholson (Archives of Toxicology, 1989)